Workload and Creative Performance: The Buffering Role of Intrinsic Motivation - Idrovo, Mercedes Narcisa; Meza Villanueva, Yirsa; Flores Carrera , Stephanie (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to examine the effect of workload on creative performance and to test whether intrinsic motivation buffers the potential negative impact of workload among employees in Colombia.Methods and Materials: A descriptive correlational research design was employed with a sample of 397 full-time employees from diverse organizations across Colombia, selected using Morgan and Krejcie’s sample size determination table. Data were collected using validated instruments: the Quantitative Workload Inventory, the Work Preference Inventory–Intrinsic Motivation subscale, and the Employee Creativity Scale. Descriptive statistics, Pearson’s correlation analysis, and structural equation modeling (SEM) were conducted to test the hypothesized relationships. Analyses were performed using SPSS version 27 and AMOS version 21. Model fit was assessed through multiple indices, including χ², degrees of freedom, χ²/df, GFI, AGFI, CFI, TLI, and RMSEA.Findings: Results indicated that workload was significantly and negatively correlated with creative performance (r = –.31, p < .001) and with intrinsic motivation (r = –.27, p = .001), while intrinsic motivation was strongly and positively correlated with creative performance (r = .48, p < .001). SEM analysis confirmed good model fit (χ²/df = 1.74; GFI = .94; CFI = .97; RMSEA = .043) and revealed that workload exerted a significant direct negative effect on creative performance (β = –.29, p < .001) and on intrinsic motivation (β = –.27, p < .001). Intrinsic motivation showed a robust positive effect on creative performance (β = .52, p < .001) and buffered the negative workload–creativity relationship, partially mediating and weakening the total negative impact of workload (β total = –.15, p = .041).Conclusion: Findings highlight that although heavy workload reduces employees’ creativity, fostering intrinsic motivation can protect and sustain innovative performance under job demands. Organizations should design roles and climates that support autonomy, curiosity, and self-driven engagement to maintain creativity despite high workload conditions.